2002
DOI: 10.1111/j.1572-0241.2002.05586.x
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Undetected Ulcerative Colitis: Data From The Nottingham Fecal Occult Blood Screening Trial

Abstract: In comparison with detected disease, undetected ulcerative colitis is relatively common but does usually cause some symptoms. It generally appears to follow a benign course, but a significant proportion have extensive colitis and may therefore be at an increased risk of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…These findings are likely relevant to human IBD where genetic risk, while necessary, is by itself insufficient to cause frank disease. It is also possible that a significant number of these at-risk subjects have subclinical disease that would be detectable histologically or through examination of immune/inflammatory markers, which has been previously suggested (Howarth et al, 2002; Sakata et al, 2001). Moreover, these individuals are likely to be more sensitive to risk factors that set the stage for events that trigger the immune response to cause frank clinical disease.…”
Section: Discussionmentioning
confidence: 96%
“…These findings are likely relevant to human IBD where genetic risk, while necessary, is by itself insufficient to cause frank disease. It is also possible that a significant number of these at-risk subjects have subclinical disease that would be detectable histologically or through examination of immune/inflammatory markers, which has been previously suggested (Howarth et al, 2002; Sakata et al, 2001). Moreover, these individuals are likely to be more sensitive to risk factors that set the stage for events that trigger the immune response to cause frank clinical disease.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, our exploratory study indicates that SEPT9 may be able to identify potentially curable early cancers or even precancerous colorectal lesions in asymptomatic individuals. However, patients with concomitant inflammatory diseases or other increased cancer risk should be directed to colonoscopy according to current clinical routine without non-invasive first line screening [21], [22].…”
Section: Discussionmentioning
confidence: 99%
“…A large European study of incidence of IBD actively excluded asymptomatic cases and those identified during a screening activity. 16 An early UK colorectal screening programme 17 FOBt. This equates to 2-2.5% of those undergoing investigation for positive FOBt, similar to the proportion in this study.…”
Section: Discussionmentioning
confidence: 99%